ANALISIS KANDUNGAN FOSFOR SEDIMEN TAMBAK INTENSIF UDANG VANAME YANG DIFERMENTASI OLEH BAKTERI LIMBAH CAIR NANAS SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA LEMBAR KEGIATAN PESERTA DIDIK (LKPD) KELAS XII MATERI BIOTEKNOLOGI - Eka Reza Rifai; Agus Sutanto; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
This research aims to know P (phosphor) content of compost fertilizer sediment ponds vaname shrimp was fermented by LCN and utilization of this research is to make Worksheet Students material biotechnology. This research used 1 control (without treatment) and 3 treatments, KA (5 LCN bacteria), KB (10 LCN bacteria), and KC (15 LCN bacteria). The content of P can be seen from testing the content in the Chemical Laboratory University of Muhammadiyah Malang. The phosphor content of compost fertilizer sediment ponds vaname shrimp is relatively low, and this value has not reached, the threshold that has been determined by the Agricultural Minister. The results of the research can be used as a source of learning for Worksheet Students.